Three-year delay in diagnosis of pulmonary sarcoidosis due to presence of necrotizing granulomas: a cautionary case report - Yue, Yubing; Du, Rao; Han, Ding; Zhao, Tianxia; Zeng, Chunfang; Feng, Yinhe (Frontiers in Medicine, 2024)
Diagnosis of pulmonary sarcoidosis can be difficult and strongly dependent on clinical experience, especially when necrotizing granulomas are present. Here we report an individual who, three years after onset of symptoms, was definitively diagnosed with pulmonary sarcoidosis based on percutaneous lung biopsy under the guidance of computed tomography, after he failed to receive a specific diagnosis at other tertiary hospitals based on cervical lymph node biopsy and transbronchial needle aspiration under the guidance of endobronchial ultrasonography. After his definitive diagnosis at our medical center, he was given corticosteroids, which led to remission. Clinicians, especially in areas lacking suitably experienced pathologists, should be aware of how to diagnose sarcoidosis in the presence of abundant necrotizing granulomas in order to ensure timely diagnosis.